Willingness-to-pay for FTTH for secured and stable usage of OTT media streaming services - Tatcha Sudtasan; Hitoshi Mitomo (International Telecommunications Society (ITS), 2017)
The objective of this study is to investigate the impact of OTT media streaming services on demand for FTTH.Our approach involves analyzing data that comprise the respondents' willingness-to-pay (WTP) for FTTH. The analysis decomposes the WTP by individual characteristics and OTT media service consumption as well as the connection problem experience and expectation of media consumption through the Internet. Respondents are allowed to express their willingness-to-pay for FTTH in a range in order to truly reflect their willingness and flexibility to pay. Coefficients from independent variables are interpreted as a change in the amount of willing-to-pay influenced by the marginal increase of significant variables. The result shows that consumers are willing to pay for FTTH for the secured and stable usage of OTT media streaming services especially movies through the Internet. This study contributes to the projection of market value and the marginal effect of OTT media streaming services on the expansion of the FTTH market. Policy implications are discussed to set regulations that increase broadband penetration at the right price incentives.
Keywords: 330; Optical fiber; Willingness to pay; Over-the-Top (OTT); Media streaming services; Price regulation